# Integrate $\int \frac{ e^{\tan^{-1}x}}{(1+x^2)^2} dx$ [closed]

How do I carry out the integration $$\int \frac{ e^{\tan^{-1}x}}{(1+x^2)^2} dx$$

The answer, from Wolfram Alpha is $$e^{\tan^{-1}x}\left ( \frac 2 5 + \frac {2x+1} {5(x^2+1)} \right)$$

## closed as off-topic by Carl Mummert, colormegone, Shailesh, Bobson Dugnutt, John BMar 12 '16 at 0:08

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Carl Mummert, colormegone, Shailesh, Bobson Dugnutt, John B
If this question can be reworded to fit the rules in the help center, please edit the question.

• you want to use a substitution $u = \tan^{-1} x$ so $du = \frac{dx}{1+x^2}$, not sure how to get rid of the second $(1+x^2)$ in the denominator – gt6989b Mar 11 '16 at 14:54
• What is your motivation for studying this integral? Moreover, if you already know the antiderivative, then you do know how to carry out the integral - is there some more general family of integrals in which you are interested? – Carl Mummert Mar 11 '16 at 19:15
• I know the antiderivative, but I do not know how to carry out the integral. – anukul Mar 12 '16 at 7:05
• The antiderivative is/contains a product, so one real possibility is to use integration by parts. Look at the product to determine $u$ and $dv$. – Rory Daulton Mar 14 '16 at 12:58

Let $\displaystyle I=\int\frac{e^{\tan^{-1}x}}{(1+x^2)^2}dx$, and integrate by parts with $\displaystyle u=\frac{1}{x^2+1}$ and $\displaystyle dv=\frac{e^{\tan^{-1}x}}{1+x^2}dx$ to get

$\hspace{.8 in}\displaystyle I=\frac{e^{\tan^{-1}x}}{x^2+1}+2\int\frac{x e^{\tan^{-1}x}}{(1+x^2)^2}dx$. $\;\;\;(1)$

Now integrate by parts with $\displaystyle u=\frac{x}{x^2+1}$ and $\displaystyle dv=\frac{e^{\tan^{-1}x}}{1+x^2}dx$ to get

$\;\;\;\displaystyle \int\frac{x e^{\tan^{-1}x}}{(1+x^2)^2}dx=\frac{x e^{\tan^{-1}x}}{x^2+1}-\int\frac{e^{\tan^{-1}x}}{(1+x^2)^2}dx+\int\frac{x^2 e^{\tan^{-1}x}}{(1+x^2)^2}dx$

$\displaystyle\hspace{1.3 in}=\frac{x e^{\tan^{-1}x}}{x^2+1}-\int\frac{e^{\tan^{-1}x}}{(1+x^2)^2}dx+\int\frac{e^{\tan^{-1}x}}{1+x^2}dx-\int\frac{e^{\tan^{-1}x}}{(1+x^2)^2}dx$

$\displaystyle\hspace{1.3 in}=\frac{x e^{\tan^{-1}x}}{x^2+1}-2I+e^{\tan^{-1}x}$

Substituting in (1) gives

$\displaystyle\hspace{1.3 in}I=\frac{e^{\tan^{-1}x}}{x^2+1}+\frac{2x e^{\tan^{-1}x}}{x^2+1}-4I+2e^{\tan^{-1}x}$,

so $\displaystyle\hspace{1.1 in}I=\frac{1}{5}\left[\frac{e^{\tan^{-1}x}}{x^2+1}+\frac{2x e^{\tan^{-1}x}}{x^2+1}+2e^{\tan^{-1}x}\right]+C$

$\displaystyle\hspace{1.4 in}=\frac{1}{5}e^{\tan^{-1}x}\left[\frac{2x+1}{x^2+1}+2\right]+C$.

Notice that $\tan^{-1}(x)$ and $1/(1+x^2)$ appear in your integrand. This means a $u$-substitution with $\tan^{-1}(x)$ could be useful.

$$\int \frac{e^{\tan^{-1}(x)}}{(1+x^2)^2}dx$$

Let $u=\tan^{-1}(x)$ then $du = \frac{1}{1+x^2}dx$ and $x = \tan(u)$. So the integral becomes:

$$\int \frac{e^{\tan^{-1}(x)}}{(1+x^2)^2}dx=\int \frac{e^{u}}{1+\tan^2(u)} du$$

Recall that $1+\tan^2(x) = \sec^2(x) = 1/\cos^2(x)$ so

$$\int \frac{e^{u}}{1+\tan^2(u)} du=\int e^{u} \cos^2(u) du$$

Finally $\cos^2(u) = \frac12 (1+\cos(2u))$ and

$$\int e^{u} \cos^2(u) du=\frac12 \int (1+\cos(2u)) e^u du$$

$$\int\frac{e^{\tan^-1(x)}}{(1+x^2)dx}=\int{e^{\arctan(x)}}\cdot\frac{dx}{1+x^2}\cdot\frac{1}{1+x^2}$$ $$=\left|\arctan x=t\Rightarrow \frac{dx}{1+x^2}=dt; x=\tan t\Rightarrow 1+x^2=1+\tan^2 t=\frac{1}{\cos^2 t}\right|$$ $$=\int{e^t}\cdot dt\cdot\frac{1}{\frac{1}{\cos^2 t}}=\int e^t\cos^2 t dt=\int e^t\left(\frac{1+\cos 2t}{2}\right)dx=$$ $$=\frac{1}{2}\int e^t(1+\cos 2t)dt=\frac{1}{2}\int e^t dt+\frac{1}{2}\int e^t\cos 2tdt=\frac{e^t}{2}+\frac{1}{2}I$$ Now we have a solution of the integral: $$I=\int e^t\cos 2tdt=\left|u=e^t\Rightarrow du=e^tdt; dv=\cos 2t\Rightarrow v=\frac{\sin 2t}{2}\right|=$$ $$=\frac{e^t\sin 2t}{2}-\frac{1}{2}\int e^t\sin 2t dt=\frac{e^t\sin 2t}{2}-\frac{1}{2}I_1$$ Now solution of the integral $I_1$ $$I_1=\int e^t\sin 2tdt=\left|u=e^t\Rightarrow du=e^tdt; dv=\sin 2t\Rightarrow v=-\frac{\cos 2t}{2}\right|=$$ $$=-\frac{e^t\cos 2t}{2}+\frac{1}{2}\int e^t\cos 2t dt$$ From here we have: $$\int e^t\cos 2t dt=\frac{e^t \sin 2t}{2}-\frac{1}{2}\left(-\frac{e^t \cos 2t}{2}+\frac{1}{2}\int e^t\cos 2t dt\right)$$ $$\frac{5}{4}\int e^t \cos2t dt=\frac{e^t \sin 2t}{2}+\frac{e^t \cos 2t}{4}$$ $$I=\int e^t \cos2t dt=\frac{2e^t \sin 2t}{5}+\frac{e^t \cos 2t}{5}$$ Finally we have: $$\int\frac{e^{\arctan x dx}}{(1+x^2)2}dx=\frac{e^t}{2}+\frac{e^t\sin 2t}{5}+\frac{e^t\cos 2t}{10}$$ $$=e^t\left(\frac{1}{2}+\frac{\sin 2t}{5}+\frac{\cos 2t}{10}\right)=e^t\cdot\frac{5+2\sin 2t+\cos 2t}{10}$$ $$=e^t\cdot\frac{5+2\frac{2\tan t}{1+\tan^2 t}+\frac{1-\tan^2 t}{1+\tan^2 t}}{10}$$ $$=e^{\arctan x}\cdot\frac{5+5\tan^2 t+4\tan t+1-\tan^2 t}{10(1+\tan^2 t)}$$ $$=e^{\arctan x}\cdot\frac{6+4\tan t+4\tan^2 t}{10(1+\tan^2 t)}=e^{\arctan x}\cdot\frac{3+2\tan t+2\tan^2 t}{5(1+\tan^2 t)}$$ $$=e^{\arctan x}\cdot\frac{3+2x+2x^2}{5(1+x^2)}+C$$ I hope you help.